НЕФТНИ СУРИБ ЧИҚАРИШ ЖАРАЁНИНИ МАТЕМАТИК МОДЕЛЛАШТИРИШ ВА ДАСТУРИЙ ТАЪМИНОТИ - Бегулов, Олмос (Innovatsion texnologiyalar, 2022)
The article describes the implementation of the oil pumping process using the finite method of determining the saturation function valuyes in the issuye of two-phase filtration, appliyed to the problem of computer modeling, and the software has beyen developed. The results of the practical application of the proposed algorithms are also pretsented.